2008
DOI: 10.1007/s12010-008-8348-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interactions of Lysozyme with DNA by Surface Plasmon Resonance and Circular Dichroism Spectroscopy

Abstract: Association with nucleic acid has been recognized as a unique role of lysozyme and may explain why lysozyme was called a killer protein against HIV infection. In the present study, we characterized the interactions of lysozyme and its derived peptides with a biotin-labeled pUC19 plasmid DNA. Real-time detection of the macromolecular interaction was performed using the SPR (surface plasmon resonance) spectroscopy. The SPR sensorgrams were analyzed and the association and dissociation rate constants as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
(32 reference statements)
1
19
0
Order By: Relevance
“…Besides its direct antibacterial enzymatic activity, lysozyme displays other promising biological properties, which may enable its therapeutic use as an immune-modulating agent in the near future. For example, lysozyme has remarkable nucleic acid-binding properties, which may explain its antiviral activity toward HIV-1 [11,12,13]. Moreover, the ability to stimulate the recovery of lymphocyte CD4+/CD8+ ratio in patients in remission after chemotherapy for malignant diseases [14], and to beneficially act in the context of human ageing [15], further highlights the multifaceted immune-modulating properties of this natural product.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its direct antibacterial enzymatic activity, lysozyme displays other promising biological properties, which may enable its therapeutic use as an immune-modulating agent in the near future. For example, lysozyme has remarkable nucleic acid-binding properties, which may explain its antiviral activity toward HIV-1 [11,12,13]. Moreover, the ability to stimulate the recovery of lymphocyte CD4+/CD8+ ratio in patients in remission after chemotherapy for malignant diseases [14], and to beneficially act in the context of human ageing [15], further highlights the multifaceted immune-modulating properties of this natural product.…”
Section: Introductionmentioning
confidence: 99%
“…Early investigation of this protein found that its positive charge rather than its enzymatic activity accounts for its antiviral action [21]. Lysozyme and lysozyme-derived peptides exhibit DNA-binding activity, and previous researchers have suggested that the interaction between lysozyme and DNA molecules may interfere with DNA replication, modulate gene expression, and block bacterial and viral infections, contributing to the proteins' innate immune modulating activity [22]. These proteins are also known to be opsonic in nature and to have the ability to activate the complement system and increase phagocytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…SPR spectroscopy makes possible real-time detection and the determination of binding kinetics and affinities of biomacromolecular interactions2728.…”
Section: Resultsmentioning
confidence: 99%